Enhanced controller for a four-leg inverter operating in a stand-alone microgrid with unbalanced loads - Effat Ayoubi; Mohammad Reza Miveh; Ali Asghar Ghadimi; Sajad Bagheri (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
Stand-alone low voltage (LV) microgrids supplying small local loads far from the utility grid are becoming an increasingly popular alternative to a total reliance on the centralized utility grid. In most of LV microgrids, three-phase four-wire distribution systems are used to supply both single- and three-phase loads. Unequal distribution of loads can result in voltage unbalance problems. The use of the four-leg inverter is one of the best solutions for providing a neutral current path and compensating unbalanced load conditions in stand-alone LV microgrids. This paper proposes a fast control technique to compensate unbalanced voltage conditions for a four-leg inverter operating in a stand-alone LV microgrid. The suggested technique provides the current controller’s orthogonal component without introducing any additional dynamics or distortions. The major benefits of the recommended per-phase control technique over conventional orthogonal signal generation (OSG) methods are enhanced steady-state and dynamic performances as well as independency to the system parameters. Several simulation results are provided to confirm the superior performance of the suggested methods.